2014
DOI: 10.1128/cvi.00544-13
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Antigenic Typing of Seasonal Influenza Virus Breakthrough Cases from a 2008-2009 Vaccine Efficacy Trial

Abstract: Estimations of the effectiveness of vaccines against seasonal influenza virus are guided by comparisons of the antigenicities between influenza virus isolates from clinical breakthrough cases with strains included in a vaccine. This study examined whether the prediction of antigenicity using a sequence analysis of the hemagglutinin (HA) gene-encoded HA1 domain is a simpler alternative to using the conventional hemagglutination inhibition (HI) assay, which requires influenza virus culturing. Specimens were take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
(58 reference statements)
0
3
0
1
Order By: Relevance
“…However, a comparison of antigenic and genetic maps showed that the antigenic impact of genetic changes varies. Thus, not all amino acid substitutions in HA sequences, including those at ABSs, equally affect antigenic properties [ 315 , 316 ]. An ideal sequence-based strategy for vaccine strain selection is to quantify antigenic distances directly using protein sequences (Fig.…”
Section: Influenzamentioning
confidence: 99%
“…However, a comparison of antigenic and genetic maps showed that the antigenic impact of genetic changes varies. Thus, not all amino acid substitutions in HA sequences, including those at ABSs, equally affect antigenic properties [ 315 , 316 ]. An ideal sequence-based strategy for vaccine strain selection is to quantify antigenic distances directly using protein sequences (Fig.…”
Section: Influenzamentioning
confidence: 99%
“…The third vaccine is intranasally applied and consists of live-attenuated influenza viruses [ 17 , 18 ]. Surveillance studies over the past 15 years have revealed that next to the circulating A/H1N1 and A/H3N2 viruses, two antigenically distinct B virus types circulate: the so called B/Yamagata and B/Victoria lineages [ 19 , 20 ]. One of these two B lineage viruses tends to be dominant over the other during seasonal influenza.…”
Section: Introductionmentioning
confidence: 99%
“…Sequence similarity is insufficient to predict antigenic properties (Durviaux et al 2014;Lee et al 2007a;Lees et al 2010;Liao et al 2008). Structural similarity and physical chemistry attributes of the HA provide additional information to estimate the degree of antigenic similarity between related viruses.…”
Section: Perspectivesmentioning
confidence: 99%